Investigar em Psicanálise? : Contributos Teórico-Metodológicos a Partir de uma Investigação Conceptual Sobre a Contratransferência - Falcão Rosado, Filipa (2024)
Research in psychoanalysis?Theoretical-methodological Contributions from a Conceptual Investigation on Countertransference   There has been an ongoing debate regarding the scientific status of psychoanalysis, its research methods, and knowledge production. From a pluralist perspective of science, it is argued that research methods and instruments need to be adequate to the specificity of the object of study. Thus, from an ontological point of view, psychoanalysis is based on a conception of the psychic that presupposes a divided, conflictual and defended subject. Based on ongoing conceptual research of the clinical use of the concept of countertransference, we sought to construct a device appropriate to the phenomenon under research, using a psychoanalytically informed methodology. We used the Free Association Narrative Interview (FANI) and the dynamics established in the research group during the analysis of the material to gain access to the implicit meanings of the concept. The processes underlying the procedure used for analysing the interviews were discussed and explained using Bion’s theory of thinking, namely the concepts of negative capacity, alpha dream work and selected fact. This paper aims to make theoretical and methodological contributions to the clarification of research in psychoanalysis outside the analytic room.